Delving into the world of webCHAT – an e-mental health support service for distressed youths in Singapore - Yi Ping Lee; Ying Ying Lee; Hamidah Binte Otheman; Charmaine Tang; Mythily Subramaniam; Swapna K Verma (Digital Health)
Background Young people face high rates of mental health issues, yet many do not seek professional help. In 2017, CHAT launched webCHAT – a free, anonymous, one-on-one synchronous web-based text service managed by case managers (CMs) to support young people aged 16 to 30 who may be hesitant about engaging in face-to-face mental health services. Objective This study aimed to explore the perspectives and experiences of users who accessed webCHAT for mental health support in Singapore. Methods A qualitative thematic analysis was conducted using transcripts of webCHAT sessions to identify main themes. Results Many users accessed webCHAT to seek support with emotional and behavioural concerns, valuing its immediacy and anonymity over traditional appointment-based services. A desire to ‘get better’ and self-realisation emerged as important motivators for seeking help, with webCHAT offering a supportive space for reflection. Key barriers to seeking additional support included fear of stigma, concerns about leaving a ‘medical record’, potential hospitalisation, and treatment costs. Conclusions webCHAT appears to be a viable early intervention and preventive approach, providing young people with a pathway towards in-person support services. Professional guidance from CMs is essential in encouraging users to pursue further support, emphasising the importance of human expertise in digital mental health platforms. By fostering early help-seeking and self-realisation, webCHAT has the potential to reduce the long-term impact of mental health challenges. Future research could explore webCHAT's long-term effects and identify improvements to facilitate users’ transitions to in-person support.